Growing spaces: an evaluation of the mental health recovery programme using mixed methods. (September 2018) - Howarth, Michelle; Rogers, Michaela; Withnell, Neil; McQuarrie, Cath
Background: Therapeutic horticulture is a nature-based method that includes a range of green activities, such as gardening, to promote wellbeing. It is believed that therapeutic horticulture provides a person-centred approach that can reduce social isolation for people with mental health problems. Aims: The aim of the project was to evaluate the impact of a mental health recovery programme that used therapeutic horticulture as an intervention to reduce social inclusion and improve engagement for people with mental health problems. Methods: A mixed-methods approach was used and data from four semi-structured focus group interviews, 11 exit interviews and 20 'recovery star' datasets were collected from September 2015 to October 2017. Qualitative data from the interviews were thematically analysed, and quantitative data based on a recovery star outcomes tool were analysed using descriptive statistics to demonstrate trends and progression. The findings were then triangulated to provide a rich picture of the impact of the mental health recovery programme. Results: The recovery star data indicated that participants were working towards self-reliance. Qualitative data from the exit interview and semi-structured focus groups found similar results. The triangulated findings highlight that the mental health recovery programme enabled participant integration into the community through providing a space to grow and build self-confidence while re-engaging with society. The results suggest that using therapeutic horticulture as an intervention within the mental health recovery programme can support people with mental health problems to re-engage socially. Nature-based activities could be used within the 'social prescribing' movement to encourage partnership working between the NHS and voluntary sector organisations which can complement existing mental health services. Conclusion: The use of therapeutic horticulture as an intervention within a mental health recovery programme can support people with mental health problems to re-engage with the community and is integral to the rehabilitation process. The mental health recovery programme should be promoted within the social prescribing movement as an evidence-based opportunity to support people in the community.